2016
DOI: 10.1038/srep36447
|View full text |Cite
|
Sign up to set email alerts
|

ROR1 is a novel prognostic biomarker in patients with lung adenocarcinoma

Abstract: Currently, there is no reliable biomarker to clinically predict the prognosis of lung adenocarcinoma (ADC). The receptor-tyrosine-kinase like orphan receptor 1 (ROR1) is reported to be overexpressed and associated with poor prognosis in several tumors. This study aimed to examine the expression of ROR1 and evaluate its prognostic significance in human lung ADC patients. In this present study, Western blot analysis and immunohistochemistry were performed to characterize expression of ROR1 protein in lung ADC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 37 publications
(52 reference statements)
3
45
3
Order By: Relevance
“…The distribution of ROR1 was homogeneous among the different mutational categories; in particular, we found no association of ROR1 expression and the presence of EGFR or KRAS mutations. Moreover, we did not nd any correlation between ROR1 and TTF-1 expressions, unlike suggested by other authors in an Asian population [21] (Table 2). Parallel statistical evaluations demonstrated that, in our patient cohort, there were no differences in OS of patients with EGFR mutated lung adenocarcinoma versus those with EGFR wild-type tumors, irrespective of the stage (p = 0.9875).…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…The distribution of ROR1 was homogeneous among the different mutational categories; in particular, we found no association of ROR1 expression and the presence of EGFR or KRAS mutations. Moreover, we did not nd any correlation between ROR1 and TTF-1 expressions, unlike suggested by other authors in an Asian population [21] (Table 2). Parallel statistical evaluations demonstrated that, in our patient cohort, there were no differences in OS of patients with EGFR mutated lung adenocarcinoma versus those with EGFR wild-type tumors, irrespective of the stage (p = 0.9875).…”
Section: Resultscontrasting
confidence: 95%
“…The results of a study by Zheng and colleagues revealed that ROR1 protein expression was signi cantly higher in lung AC tissue than in the adjacent normal tissue. Furthermore, patients with advanced disease showed higher levels of ROR1 expression, and this study revealed an association between high ROR1 expression and worse OS [21].…”
Section: Discussionsupporting
confidence: 52%
“…In survival analysis, although only LDH level was recognized as an independent indicator of DLBCL prognosis in multivariate analysis, ROR1 expression, B symptoms and LDH level were found to be remarkably associated with the overall survival of DLBCL patients by univariate mode. Our results are consistent with previous studies on the prognostic role of ROR1 in other types of human cancers .…”
Section: Discussionmentioning
confidence: 71%
“…The orphan receptor tyrosine kinase ROR1 is a transmembrane glycoprotein with high expression during embryonic and fetal development, while with little expression in adult tissues [9]. Recently, high ROR1 expression was also observed in acute lymphocytic leukemia [20], chronic lymphocytic leukemia [21], ovarian cancer [14, 22], gastric cancer [23], breast cancer [13] and lung cancer [10]. But there is a lack of exploration on ROR1 expression in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…ROR1 is primarily expressed during embryonic and fetal development, whereas it is absent in most mature tissues [8, 9]. Recently, ROR1 expression was reported to elevate in human leukemia and a variety of solid malignancies [1014], suggesting that ROR1 may serve as a potential target for cancer therapy. Furthermore, higher expression of ROR1 is associated with more aggressive and poorer prognosis in breast, ovarian and lung cancers, in which ROR1 regulates expression of genes involved in epithelial-mesenchymal transition (EMT) [15].…”
Section: Introductionmentioning
confidence: 99%